"Sleeping Beauty Syndrome" and Psychosis as Precursory Symptoms of Multiple Sclerosis: A Rare Case and Literature Review. Issue 12 (December 2021) - Evagorou, Olympia; Arvaniti, Aikaterini; Angelopoulou, Christina; Mavraki, Eleni; Mikellides, Georgios; Samakouri, Maria
Abstract : Abstract: Frequently, patients with multiple sclerosis (MS) experience comorbid psychiatric symptoms. Mental disorders primarily occur simultaneously with or after an MS diagnosis; however, the probability of them being the initial manifestation of the disease is rare. We describe the case of a 22-year-old man who had previously been hospitalized because a single psychotic episode alongside symptoms of Kleine-Levin syndrome and a diagnosis of "acute and transient psychotic disorders." Two years later, he was diagnosed with MS. A literature review of the possibility of a psychiatric episode overshadowing an MS diagnosis is then presented. Clinicians should always consider the possibility of an underlying organicity in a case of psychiatric presentation with atypical features, with special attention being given during the investigation process. This approach will lead to the early diagnosis of an organic disease, which can be treated accordingly and as early as possible.